Exploring attendance at emergency departments for children with non-urgent conditions in Turkey: a qualitative study of parents and healthcare staff perspectives. Issue 2 (9th June 2022) - Butun, Ahmet; Lynn, Fiona; McGaughey, Jennifer; McLaughlin, Katrina; Linden, Mark
Abstract: Background: Overcrowding in Emergency Departments (EDs) is a significant global concern with negative consequences for patients, healthcare staff, and healthcare systems. The use of EDs by parents of children with non-urgent conditions is associated with overcrowding, higher healthcare costs, lower quality of care, and longer waiting times. Research in this area has largely been conducted in high-income countries, with a dearth of work originating in middle and low-income regions. The aim of this study was to explore the reasons for parents attending EDs with their child for non-urgent conditions in Turkey. Method: Semi-structured interviews were conducted with 13 parents, 15 ED staff, and 10 General Practitioners (GPs) in 2 regions of Turkey between March and May 2017. Data were analyzed using the principles of grounded theory. Results: The findings were classified into 5 core categories: (1) parents' feelings, knowledge, and perceived inability to provide self-care; (2) perceived limitations of healthcare services, system, and staff; (3) parents' preferences for hospital and ED services; (4) adverse impact on ED services; and (5) perceived needs for care. Conclusion: This is the first study conducted in a middle-income country regarding parental reasons for using the ED for nonurgent conditions. Greater efforts must be made to reduce unnecessary visits to the ED to better meet service user needs and to increase the satisfaction of both parents and healthcare staff. The findings of this study may inform healthcare providers, policymakers, healthcare staff, and researchers to design interventions in order to mitigate overcrowding in the ED.